Total Synthesis and Stereochemical Assignment of Baringolin1. Issue 30 (18th June 2013) - Just‐Baringo, Xavier; Bruno, Paolo; Ottesen, Lars K.; Cañedo, Librada M.; Albericio, Fernando; Álvarez, Mercedes
<x xml:space="preserve">Abstract</x> The thiopeptide antibiotic baringolin has been synthesized, and its structure and stereochemistry have been confirmed. The use of a strategy based on palladium‐catalyzed cross‐couplings permitted a modular construction of this natural product.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>